2014
DOI: 10.3109/03639045.2014.891129
|View full text |Cite
|
Sign up to set email alerts
|

Development of topical hydrogels of terbinafine hydrochloride and evaluation of their antifungal activity

Abstract: The purpose of this study was to prepare hydrogels and microemulsion (ME)-based gel formulations containing 1% terbinafine hydrochloride (TER-HCL) and to evaluate the use of these formulations for the antifungal treatment of fungal infections. Three different hydrogel formulations were prepared using chitosan, Carbopol® 974 and Natrosol® 250 polymers. A pseudo-ternary phase diagram was constructed, and starting from ME formulation, a ME gel form containing 1% Carbopol 974 was prepared. We also examined the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Not only must they provide moisture to the injury, but also gel formulation must maintain drug stability during shelf time as well as an appropriate release during their administration. Several works have demonstrated that during hydrogel formulation, different excipients have variations in drug release . With regards to chemical stability, SOSs and chlorine can be exhausted into hydrogel because their high reactivity ; this idea is supported by our results because chlorine containing and SOSs were less effective against biofilm formation and elimination than DADS‐M or biguanide.…”
Section: Discussionsupporting
confidence: 77%
“…Not only must they provide moisture to the injury, but also gel formulation must maintain drug stability during shelf time as well as an appropriate release during their administration. Several works have demonstrated that during hydrogel formulation, different excipients have variations in drug release . With regards to chemical stability, SOSs and chlorine can be exhausted into hydrogel because their high reactivity ; this idea is supported by our results because chlorine containing and SOSs were less effective against biofilm formation and elimination than DADS‐M or biguanide.…”
Section: Discussionsupporting
confidence: 77%
“…The optimal MBH formulations O2, O4, O6, O8, and plain drug solution were assayed for antifungal activity against strains of Actinomyces, Candida, Rhizopus, and Sacchromyces species. The fungal culture suspensions were made according to the ATCC protocol of microbiologics and they were incubated for 24 h to establish the growth of fungi before transferring onto the solid agar medium as the strain was available in lyophilized form (Celebi et al 2015). The sterile petri-dishes were filled with agar growth medium and allowed to solidify.…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%
“…The dispersions were kept at 4 °C for 24 h for complete swelling of the polymer. The aqueous dispersions of carbopol 940 were slowly mixed with sulpiride ME under stirring at 1000 rpm and were allowed to homogenize for 10 min; then the mixtures were titrated with triethanolamine to pH 6-6.5 to obtain MBGs [8,9].…”
Section: Preparation Of Mucoadhesive Microemulsion Based Gel (Mbg)mentioning
confidence: 99%
“…This may be due to the fact that all formulation compositions were of generally recognized as safe (GRAS) category [15]. This difference in release could be attributed to the different viscosity of the formulations [8]. In general, a formulation that possesses lower viscosity, expected to exhibit faster release of active ingredients [30].…”
Section: Nasal Ciliotoxicity Studymentioning
confidence: 99%